La Traduction en tant que discours - Walkiewicz, Barbara (Wydawnictwo Naukowe UAM, 2012)
Every translation is a second-order discourse, based on a first-order discourse, whose form is the result of negotiation between the discursive polysystems of the source and target cultures. Its dual role, representing the source-language discourse in the target culture as well as meeting the intended expectations of the target text receiver, inevitably entails the intervention of the translator as a second-order communicating subject, as will be illustrated using a French translation of a building design.
Translation as a discourse
Keywords: translation; discourse; discursive polysystem; building design